Philologia inter Disciplinas: The Department of Classics at St Petersburg University 1819–1884 - Verlinsky, Alexander (Hyperboreus, 2014)
The author surveys the history of the Department of Classics at St Petersburg University from 1819 to 1884 – from its humble beginnings to its impressive growth in the course of the classicizing reform. Stress is laid on different tendencies in Classical philology (Wortphilologie versus Altertumswissenschaft) as mirrored in teaching and scholarship within the department as well as on the complicated but ever fruitful relations between classical philologists and ancient historians at the time.